MHC Class I diversity influences haematozoon infection intensity in the polymorphic black sparrowhawk (Accipiter melanoleucus) - Le Roux, Liezl (Percy FitzPatrick Institute of African Ornithology, 2015)
The major histocompatibility complex (MHC) is a multigene family known to be the most variable gene group in vertebrates in terms of allelic diversity and gene number. Pathogen mediated selection is thought to be the major driving force behind the unusually high levels of MHC polymorphism in natural populations. In this study the relationship between MHC class I diversity and blood parasite infection intensity is explored in a population of black sparrowhawks (Accipiter melanoleucus). The species is of particular ecological and evolutionary interest as black sparrowhawks display a discrete polymorphism in plumage pattern across its range, occurring as a light and dark morph. It is well established in birds that carotenoïd and melanin-based pigmentation patterns are often associated with parasite resistance. In this study, functional variation at the peptide binding region (PBR) of MHC class I loci is investigated to explain individual variation in blood parasite infection in black sparrowhawks. Using DNA sequence data together with individual estimates of blood parasite load (for Haemoproteus nisi and Leucocytozoon toddi); the study tested the relationship between (i) allelic diversity and individual parasite load and (ii) specific alleles and individual parasite load using a Generalized Linear Model framework. Seven different, putatively functional, MHC class I alleles were identified. Number of alleles per individual ranged from one to three in individuals infected with H. nisi, whereas individuals infected with L. toddi had either two or three different alleles. A significant positive association was found between H. nisi infection intensity and MHC allele Acme_BF2*03. No significant association was found between L. toddi infection intensity and a specific allele. The results reported support the role of pathogen mediated selection of genetic variation at evolutionary relevant MHC genes through rare allele advantage. By characterizing the variation at MHC class I loci and testing for a relationship with parasitemia, it is now possible to elucidate the mechanisms and significance of MHC molecular adaptation in the black sparrowhawk.